In silico screening of naturally derived dietary compounds as potential butyrylcholinesterase inhibitors for Alzheimer’s disease treatment - Md. Tarikul Islam; Md. Aktaruzzaman; Chandan Barai; Farhan Ishrak Rafi; Al Riyad Hasan; Tasfiah Tasnim; Parvej Sarder; Ghadeer M. Albadrani; Muath Q. Al-Ghadi; Amany A. Sayed; Mohamed M. Abdel-Daim; Humayra Afroz Dona; et al. (Scientific Reports)
Abstract Alzheimer’s disease (AD) is a progressive neurodegenerative condition that causes a substantial decline in cognitive functions and affects memory, thinking abilities, and daily behavior. The most prominent hallmark of AD pathogenesis is the formation of amyloid-β plaques, among other associated pathways such as neurofibrillary tangles, mitochondrial dysfunction, neuroinflammation, and oxidative stress. Butyrylcholinesterase (BuChE), an acetylcholine-degrading enzyme, plays a critical role in the progression of Alzheimer’s disease, particularly through its involvement in amyloid-β plaque formation. Thus, the inhibition of BuChE is considered a valuable therapeutic strategy for the management of AD. The present study aimed to identify potential bioactive chemicals from naturally occurring dietary compounds that could improve neurocognitive function and appear as a viable treatment for AD by inhibiting the function of BuChE. A small library of 44 natural dietary chemicals from a variety of dietary plants was subjected to comprehensive in silico studies, including molecular docking, molecular mechanics generalized born surface area (MM-GBSA) calculations, pharmacokinetics assessments, toxicity profiles, molecular dynamics (MD) simulation, and density functional theory (DFT) analysis. These studies revealed that CID 129886986 and CID 115269 showed stronger binding affinities with drug-likeness and no toxicity than the FDA-approved standard drug, Donepezil. Additionally, they exhibited strong structural stability with fewer fluctuations throughout the simulation, making them promising candidates for Alzheimer’s disease treatment.